Bovine Leukaemia‐virus infection in Costa Rica - BONILLA, J. A. (1995)
The geographical distribution of bovine leukaemia‐virus (BLV)‐infected herds in Costa Rica and the isolation of BLV from cases of enzootic bovine leukosis are presented. It was found that BLV is prevalent throughout the country, affecting mostly dairy cattle (Bos taurus) located in the highlands around the central valley of Costa Rica. By contrast, beef cattle (Bos indicus) raised in the lowlands were affected to a lesser extent. One out of four isolates of BLV obtained from local cattle with lymphosarcomatous tumours was analysed and had similar physical, serological and biological characteristics to a reference strain of BLV isolated in the USA. However, different patterns of recognition of BLV‐protein p24 were observed among naturally infected cattle using the western‐blotting technique.